2018
DOI: 10.1096/fj.201801167rr
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of E‐box binding USF‐1 by PI3K/AKT enhances its transcriptional activation of the WBP2 oncogene in breast cancer cells

Abstract: WW domain binding protein 2 (WBP2), a transcriptional coactivator, plays a vital role in breast tumorigenesis. It positively regulates estrogen receptor, Hippo, and Wnt pathways, which subsequently enhance the transcription of downstream target genes contributing to cancer. Understanding the regulation of the expression and activity of WBP2 oncoprotein has implication in cancer therapy. We have previously reported that WBP2 is regulated at the post-translational and post-transcriptional levels. However, its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Our lab further showed that USF-1 phosphorylation/ activation is necessary for its transcriptional activation of WBP2 expression and the former was mediated by the PI 3 K/Akt pathway in response to insulin stimulation [51]. Taken together with the previous findings that WBP2 positively regulates PI 3 K/Akt pathway, the presence of a positive feedback loop between PI 3 K/Akt and WBP2 is envisaged to drive cancer processes.…”
Section: Transcriptional Regulation Of Wbp2 By An Oncogenic Transcripsupporting
confidence: 68%
See 2 more Smart Citations
“…Our lab further showed that USF-1 phosphorylation/ activation is necessary for its transcriptional activation of WBP2 expression and the former was mediated by the PI 3 K/Akt pathway in response to insulin stimulation [51]. Taken together with the previous findings that WBP2 positively regulates PI 3 K/Akt pathway, the presence of a positive feedback loop between PI 3 K/Akt and WBP2 is envisaged to drive cancer processes.…”
Section: Transcriptional Regulation Of Wbp2 By An Oncogenic Transcripsupporting
confidence: 68%
“…Since WBP2 protein is well established to be overexpressed in breast cancer [13], we reasoned the transcription factors that drive WBP2 expression would have contributed to this phenotype, at least in part. Testing this hypothesis led to the identification of upstream factor-1 (USF-1) as a novel, oncogenic transcription factor for WBP2 [51]. ChIP experiments showed that USF-1 drives WBP2 transcription by binding to the E-box of WBP2 promoter, resulting in an increase of WBP2 transcript, protein level, and breast cancer cell proliferation [51] ( Fig.…”
Section: Transcriptional Regulation Of Wbp2 By An Oncogenic Transcripmentioning
confidence: 99%
See 1 more Smart Citation
“…3a, iii). Knockdown of USF-1, the transcription factor of WBP2 23 was used as the positive control. This suggest regulation of WBP2 by MST at the post-transcriptional/ translational level.…”
Section: Mst Inhibits Wbp2-driven Breast Cancer Resulting In Good Promentioning
confidence: 99%
“…In hepatocellular carcinoma, micro non-coding RNA (miRNA) can affect the malignant phenotype of hepatocellular carcinoma cells by downregulating the expression of WBP2 [31]. The transcription factor USF1 can promote the transcription of WBP2 by binding to the E-box region of the WBP2 promoter [32]. ITCH also attenuated CD4 T-cell proliferation in mice by limiting WBP2 protein stability [33].…”
Section: Discussionmentioning
confidence: 99%